Identification of key amino acids responsible for the distinct aggregation properties of microtubule‐associated protein 2 and tau. (26th August 2015) - Xie, Ce; Soeda, Yoshiyuki; Shinzaki, Yuki; In, Yasuko; Tomoo, Koji; Ihara, Yasuo; Miyasaka, Tomohiro
Abstract: The carboxyl‐terminal sequence of tau composes the framework for its intracellular inclusions that appear in diverse neurodegenerative disorders known as tauopathies. However, microtubule‐associated protein 2 (MAP2), which contains a homologous carboxyl‐terminal sequence of tau, is undetectable in the mature tau inclusions. The mechanisms underlying this phenomenon have remained largely unknown. Here, we show that tau and MAP2 have different aggregation properties: tau aggregates to form filaments but MAP2 remains to be granules. Exchanging 221 YKPV 224 of tau (0N3R) near the PHF6 motif for 340 TKKI 343 of MAP2c profoundly changed aggregation properties, suggesting that the YKPV motif is important for filament formation, whereas the TKKI motif is for granule formation. Thus, these minimal sequences may determine the different fates of tau and MAP2 in the formation of inclusions in tauopathies. Tau and microtubule‐associated protein 2 (MAP2) are homologous microtubule‐associated proteins in neurons. So far, it is largely unknown why tau but not MAP2 is selectively involved in the filamentous inclusions (neurofibrillary tangles, NFT) formation in tauopathies, including Alzheimer's disease. In this study, we found that the difference of only two amino acids in tau and MAP2 sequences may determine their different fates in tauopathies. These results may lead to the elucidation of tau deregulation in pathological conditions. Abstract : Tau and microtubule‐associated protein 2 (MAP2) are homologous microtubule‐associated proteins in neurons. So far, it is largely unknown why tau but not MAP2 is selectively involved in the filamentous inclusions (neurofibrillary tangles, NFT) formation in tauopathies, including Alzheimer's disease. In this study, we found that the difference of only two amino acids in tau and MAP2 sequences may determine their different fates in tauopathies. These results may lead to the elucidation of tau deregulation in pathological conditions.